2016
DOI: 10.3171/2015.6.jns142695
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of sinonasal outcomes after microscopic sublabial or endoscopic endonasal transsphenoidal surgery for nonfunctioning pituitary adenomas

Abstract: obJective Both endoscopic and microscopic transsphenoidal approaches are accepted techniques for the resection of pituitary adenomas. Although studies have explored patient outcomes for each technique individually, none have prospectively compared sinonasal and quality of life outcomes in a concurrent series of patients at the same institution, as has been done in the present study. methods Patients with nonfunctioning adenomas undergoing transsphenoidal surgery were assessed for sinonasal function, quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 32 publications
6
48
0
Order By: Relevance
“…Eventually, 19 studies were included in the final analysis, enrolling 389 patients underwent microscopic transsphenoidal resection and 3458 patients with endoscopic approach. Four of which directly compared endoscopic and microscopic approaches [7][8][9][10], while the other 15 articles are single-armed studies [11][12][13][14][15][16][17][18][19][20][21][22][23], reporting purely endoscopic or microscopic transsphenoidal surgery on NFPA [11][12][13][14][15][16][17][18][20][21][22][23]. The proportion of gender, the presence of pre-operatively hypopituitarism, visual deficiency and invasive tumours were significant different between the two groups ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Eventually, 19 studies were included in the final analysis, enrolling 389 patients underwent microscopic transsphenoidal resection and 3458 patients with endoscopic approach. Four of which directly compared endoscopic and microscopic approaches [7][8][9][10], while the other 15 articles are single-armed studies [11][12][13][14][15][16][17][18][19][20][21][22][23], reporting purely endoscopic or microscopic transsphenoidal surgery on NFPA [11][12][13][14][15][16][17][18][20][21][22][23]. The proportion of gender, the presence of pre-operatively hypopituitarism, visual deficiency and invasive tumours were significant different between the two groups ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Here, a further follow‐up would be necessary. In another comparative study of microscopical and bilateral endoscopical surgery, Pledger et al found no significant difference between the late postoperative SNOT‐20 scores . Similarly, to Hong et al, they applied bilateral endoscopic techniques that may have a greater impact on QOL than the unilateral approaches, suggested in this article.…”
Section: Discussionmentioning
confidence: 99%
“…49) Many authors noted better sinonasal QOL after endoscopic approach than microscopic approach at least in short-term period after surgery. 4954) However, Pledger et al 51) reported that although patients who underwent endoscopic surgery experienced significantly fewer nasal symptoms during the first 8 weeks, by 1 year after surgery, there were no significant differences between the endoscopic and microscopic groups.…”
Section: Complicationsmentioning
confidence: 99%
“…12,14,47) Sinonasal QOL following endoscopic pituitary surgery reaches a nadir at 2 to 3 weeks and recovers by 6 weeks to 3 months postoperatively. 4951) Sinonasal QOL and overall health status are well correlated in the postoperative period, suggesting the importance of sinonasal QOL on the patient experience. 49) Many authors noted better sinonasal QOL after endoscopic approach than microscopic approach at least in short-term period after surgery.…”
Section: Complicationsmentioning
confidence: 99%